Лінгвокультурний концепт "Київ" у поетичній мові Миколи Зерова - Палаш, А. (Культура слова, 2019)
У статті здійснено лінгвокультурологічний аналіз концепту «Київ» у поезії М. Зерова; простежено формування ознак поетичного концепту; з’ясовано особливості індивідуально-авторського опису Києва. Зосереджено увагу на контекстуально-семантичній структурі лексеми Київ у сонетах М. Зерова як чільного представника неокласиків. Визначено й проаналізовано лексико-семантичні варіанти (ЛСВ) лексеми Київ: 1) місто; 2) держава; 3) державна влада; 4) жителі міста. Досліджено периферійні зони однойменного концепту, у яких наявні когнітивні коди, що конкретизують образ Києва. Схарактеризовано хронотоп Києва, який означений реальними часовими проміжками. Протиставлення описів Києва у часових площинах минулого і сучасного зумовлене тим, що сучасність поет осмислює не як тотальне оновлення старого, що було характерним для радянської поезії, а як руйнацію, а минуле – як джерело збереження духовно-морального потенціалу людини й через нього – як вихід у майбутнє. The article deals with the linguocultural analysis of the Kyiv concept in M. Zerovʼs linguistic thinking; formation of signs of poetic concept is traced; the reproduction of the description of Kyiv, the princes who ruled in the times of Kyivska Rusʼ, the individualization of the language style of M. Zerov in expressive and imaginative means; the contribution of neoclassics to the development and enrichment of the Ukrainian language is analyzed. The focus is on the contextual-semantic structure of Kyiv tokens in the language of the writer; the lexical-semantic variants (LSW) are considered: 1) the city; 2) the state; 3) state power; 4) residents of the city; given examples and analyzed LSV tokens Kyiv. The peripheral zones of the semantic-conceptual field in which there are microfields (cognitive codes) are investigated; special features of the conceptual sphere of M. Zerov; the chronotype of Kyiv, which is defined by real time intervals, is characterized; the juxtaposition of Kyiv in the two temporal planes of the past and the present is due to the fact that the present is conceived by Zerov not as a total renewal of the old, which was widespread in Soviet poetry, but as destruction, and the past – as the need to preserve the spiritual and moral potential of man and through him – as a prospect into the future.